Penguatan Kompetensi Digital Guru SMP Melalui Pelatihan Pembuatan Bahan Ajar Inovatif Berbasis Android - Ahmad Junaedi; Musdar (Rengganis Jurnal Pengabdian Masyarakat, 2026)
The community service activity was motivated by the urgent need to improve digital competency among educators, especially junior high school teachers. The aim of this activity is to improve teachers' digital competence through technical training in creating innovative Android-based teaching materials using the Canva and iSpring applications, which are expected to be used directly in the classroom learning process.. In addition, this activity aims to improve teacher creativity in designing more interesting and interactive learning media. This activity was attended by 32 teachers from SMPN 4 Majene, and was held for 3 days in September 2025. The activity implementation methods include: 1). Survey of participant needs and initial assessment; 2). Preparation and distribution of training modules; 3). Implementation of offline training with a learning-by-doing approach; 4). Direct practice session on creating Android-based teaching material applications using a simple, user friendly platform; 5). Mentoring and evaluation of the results of the development of digital teaching materials by participants. The activity was carried out collaboratively by involving school partners, with support from experts in the field of educational technology, so that it could improve teachers' digital skills from 48.82 to 82.35 after participating in the training.